ANALISIS KINERJA GURU SMK ALKHAIRAAT PARIGI KECAMATAN PARIGI KABUPATEN PARIGI MOUTONG - Fatmah, Siti (Katalogis, 2015)
The purpose of this study is to reveal and describe the performance of teachers of SMK Alkhairaat Parigi who studied based on the theory of Stephan Robbin using three concepts / factors: 1) knowledge (knowing to do) focuses on the knowledge of a teacher in carrying out his duties as an educator, 2) skills (the ability to do) focuses on the skills of a teacher in designing a learning so interesting and not boring, to him it must have good skills when they wanted to teach, and 3) motivation (motivation to do) focuses on teacher motivation in their activities in school or while teaching in the classroom. Motivation is the internal motivation and external motivation. This type of research is qualitative research with selected informants making 5 people (the foundation, principals, supervisors, teachers and students of SMK Alkhairaat Parigi. The results showed that the performance of teachers smk Alkhairaat Parigi can already be said to be good, although with all the limitations of human resources in terms of quantity, but the quality is good enough. They also suggest the need for a comprehensive understanding of the performance improvement of teachers especially productive field.